Komodifikasi Media dan Budaya Kohe - Sumartono, Sumartono (Jurnal The Messenger, 2016)
The mass media which should serve as a channel of information, entertainment, education, and social control only able to portray itself solely as a medium of information and entertainment. Business dimension override seemed ideal dimensions that should go hand in hand. Commodification of the media has obscured the real function of the media. On behalf of the commercialization of value to media converted to market value. Not important quality of a program. Put forward is how a program backed by the financial strength or sponsorship. As a result, the commodification of the media has spawned society commodities. Society tends to be absorbed in the strength of an increasingly hegemonic pop culture with all its attributes. Lifestyle has become a commodity. Lifestyle embodied in Kohe culture.